Lipids-based drug carrier systems by dense gas technology: A review - Beh, C.; Mammucari, R.; Foster, Neil (Elsevier BV, 2012)
The use of lipids in drug delivery dates from the 1970s [1-3]. In this paper, an overview of lipid-based carrier systems encapsulating Active Pharmaceutical Ingredients (API), and their preparation by dense gas technology, is given. Lipid-based products at different stages of development (marketed commercialized products, clinical trial products, and current projects under research) and the production techniques utilizing dense gases are discussed. © 2012.